Impacts of the COVID-19 pandemic on productivity growth in Canada - Weimin Wang (Economic and Social Reports)
The COVID-19 pandemic has changed how production occurs in the economy in two ways. One is the full or partial closure of non-essential activities such as travel, hospitality, arts and entertainment, personal services, airlines, etc. The other is the widespread shift from in-office work to working from home. This Insights article depicts labour productivity growth in Canada and its sources by industry during the COVID-19 pandemic in order to examine the implications these changes may have had on the productivity performance of the economy.